Wap video streaming system (WAP-VSS) / Michele Ooi Lay Sean - Michele , Ooi Lay Sean (2004)
The project undertaken is WAP video streaming system (WAP-VSS). This proposal consists of four parts. The first part contains the project overview, scope, objectives and limitations. It is then followed by the literature review/survey done on the proposed project from various sources. In this second part, I have also discussed on the related projects, which others have done earlier. The third part of this proposal discusses on the planning and methodology to develop this proposed project. Apart from that, this part of the proposal also discusses on the project consideration, whereby what are the consideration that have been considered prior to the proposal of this project. The last part of this proposal lay out the project flow, system design, interface and also the expected result.